Influence of abiotic factors on population build up of cardamom whitefly Kanakarajiella cardamomi (David and Subramaniam) on cardamom (Elettaria cardamomum Maton) - KUMARESAN, S SELVAKUMARAN, B VASANTHARAJ DAVID, D (Journal of Spices and Aromatic Crops, 1999)
The seasonal occurrence and influence of abiotic factors on population build up of cardamom whitefly Kanakarajiella cardamomi on cardamom (Elettaria cardamomum) was assessed during 1989-1990 at Lower Pulneys in Tamil Nadu (India). K. cardamomi persisted throughout the year with a maximum egg population of 9.09 per leaf during October 1989 and a minimum of 0.33 per leaf during June and August 1990; maximum nymphal population was 8.66 per leaf during October 1989 and minimum was OA9 per leaf during August 1990. Maximum temperature and relative humidity exhibited a significant negative association with population build up of eggs and nymphs; however, none of the abiotic factors had signifiant partial correlation coefficient with egg. and nymphal population. From the multiple regression equation constructed with R' value, it was attributed that the abiotic components had only 24 and 43% influence on the population build up of K. cardamomi eggs and nymphs, respectively.